Divided Communities and Absent Voices: The Search for Autistic BIPOC Parent Blogs - Bridget Liang (Studies in Social Justice, 2022)
Both autistic adults and families of autistic children rely heavily on blogs and other digital platforms to create community and gain experiential knowledge about autism, but research on autism blogs has failed to distinguish between the perspectives of autistic adults and neurotypical parent bloggers. Furthermore, intersections in the experiences of BIPOC autistics are rarely examined. Using a content analysis with a feminist Critical Disability Studies lens, I explore six autism parent blogs from diverse demographics: a white neurotypical father, a white autistic mother in an interracial relationship, a white neurotypical mother, an Indigenous autistic trans father, a Black autistic nonbinary mother, and a Black neurotypical mother. I examine the attitudes of these bloggers to get a sampling of their opinions on autism, how they parent autistic children, and how their social location, specifically race, impacts their experiences. More intersectional research needs to be done to boost the perspectives of BIPOC autistics and the expertise of autistic parents.